Effect of Mathematics Anxiety and Student Learning Styles on Ability to Solve Mathematics Problems of Class XI Madrasah Aliyah Negeri (MAN) - Novikasari, Ifada; Pamuji, Slamet; Maulana, Muhammad Arsy (Proceeding International Conference on Science and Engineering, 2020)
The ability to solve mathematics problems is an ability needed in the learning process. Mathematic anxiety and student learning styles are among the factors that influence the success of mathematics problem-solving ability. By paying attention to mathematics anxiety and learning styles possessed by students, it is expected that the ability to solve mathematics problems will increase. This research is a field research type with an Ex Post Facto method and multiple linear regression statistical data analysis techniques. Data was collected through mathematics anxiety questionnaires, student learning style questionnaires, and mathematics problem-solving skills of students at Madrasah Aliyah level. The results show that (1) there is no significant effect of mathematics anxiety on the ability to solve mathematics problems with the tcount is 1.537 and the significance level is 0.126 ? 0.05. (2) there is a positive and significant effect of learning styles on the ability to solve mathematics problems with the value of tcount is 2.457 and a significance level of 0.015 <0.05.